Reading Galatians 6:16 in line with Paul’s contrast between the new aeon in Christ and the old aeon before the Christ event - Du Toit, Philip la G (Stellenbosch Theological Journal, 2016)
This contribution argues for viewing ‘the Israel of God’ in Galatians 6:16 as pointing to God’s people in the previous aeon before the Christ event. Prevalent interpretations of Galatians 6:16 are critiqued in view of the prevalent connotations to the terms Ἰσραὴλ and Ἰουδαῖος in the post-exilic period, Paul’s understanding of the fulfilment of Israel’s messianic hope, and the way in which Paul redefines identity in Christ and the Spirit. Galatians 6:16 is read with the third καί as a normal copulative (not epexegetically), constituting a contrast of the old aeon before or outside of Christ in the “flesh’” under the law with the new aeon in Christ and the Spirit in Galatians and beyond.